Ordförbindelser i SAOB. En undersökning av beskrivningen av kollokationer - Rosqvist, Bodil (Nordiske Studier i Leksikografi, 2010)
This paper presents a study of the treatment of collocations in the Swedish Academy Dictionary (SAOB), which is a historical dictionary describing Swedish from the year 1521 until the present day. The collocations selected in the study consist of a performative verb and a noun object. I have found that they are reasonably well covered in SAOB. They are often included both under the base (i.e. the noun) and the collocate (i.e. the verb). When the collocations are not included in SAOB I have looked for possible reasons for this.